KEPUASAN WALI SANTRI TERHADAP PELAYANAN PENDIDIKAN - Shobri, Muwafiqus; Durriyah, Durriyah; Hesham, Badrul (Jurnal Inovatif Manajemen Pendidikan Islam, 2023)
As a institution of non-formal education, the Al-Qur'an Education Park has its own challenges in attracting the interest of the student guardians. One step in attracting the interest of the student guardians is to provide satisfaction. The satisfaction of the student guardians is related to the educational services provided. TPQ An-Nur is one of the Islamic educational institutions that participate in the process of providing education services. This study aims to: (1) to determine the level of satisfaction of student guardians with educational services at the Al-Qur'an Education Park (TPQ) An-Nur Sungai Topo Sungaiteluk Village. (2) to identify the educational services at the Al-Qur'na Education Park (TPQ) An-Nur Sungai Topo Sungaiteluk Village. The research method used in this study is a mixed method with an explanatory sequential design, while the data collection techniques used are questionnaire, observation, interview, and documentation. For quantitative research, data analysis techniques used are data normality test, Pearson product moment test, t-test, and regression test with using SPSS 23, while in qualitative research uses data reduction, data presentation, and conclusions. The results of this study 1) The level of satisfaction of student guardians with educational services at TPQ An-Nur is strong, this can be seen from the correlation coefficient value (rxy = 0.744) with a significance level of a = 5 based on the interpretation guidelines, which are between 0,60 – 7.99 it shows that the level of satisfaction of the student guardians with educational services at TPQ An-Nur is strong. 2) Education services implemented at TPQ An-Nur contain 8 educational service standards, there is graduation service standards, content service, process service, educators and education personnel service, infrastructure service, management service, financing service, and assessment service.